Modelos lineares generalizados mistos e equações de estimação generalizadas para dados binário aplicados em anestesiologia veterinária - Galdino, Maicon Vinícius [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this work is to propose, compare and select statistical models based on the methodology of GLMMs and GEEs. Examine in which situations each model can be better used. Discuss about the techniques of parameter estimation, choice of the covariance matrix structure, definition and utility of the odds ratios and application in a set of data in the area of veterinary anesthesiology involving equines. The data used in this work were obtained by Taffarel (2013). The twentyfour equines used in the experiment were grouped as follows: (1) anesthetized animals (treatment 1), (2) animals anesthetized and that received prior analgesia (treatment 2), (3) animals anesthetized and underwent orchiectomy with administration of analgesics after surgery process (treatment 3) and (4) animals anesthetized and underwent orchiectomy with administration of analgesics before being operated (treatment 4). The animals were observed by five evaluators at different times: one hour before surgery or anesthetic (M1), four hours after recovery from anesthesia and before the application of analgesics in animals of treatment 3 (M2), two hours after M2 (M3) and twenty-four hours after surgery (M4). The response variable (with Bernoulli distribution) was look the flank, a common behavior in equines with abdominal pain. The treatment 3 and the moment 2 were the effects with the highest occurrence of odds ratios of the response variable (regardless of what statistical methodology used in the analysis) compared to other treatments and moments. Both statistical models fitted to the data (models 1 and 2) obtained through the EEGs and MLGMs shown to be a powerful tool to explain the response variable look flank especially regarding the selection of statistically significant covariates. In the EEG, is not required as the specification of the distribution of vectors response, it became quite advantageous statistical methods, particularly for binary data as ...

O objetivo deste trabalho é propor, comparar e selecionar modelos estatísticos baseados na metodologia dos MLGMs e das EEGs. Analisar em que situações cada modelo pode ser melhor utilizado. Discorrer sobre as técnicas de estimação dos parâmetros, escolha da estrutura da matriz de covariância, definição e utilidade das razões de chances e a aplicação em um conjunto de dados da área de anestesiologia veterinária envolvendo equinos. Os dados utilizados neste trabalho foram obtidos por Taffarel (2013). Os vinte e quatro equinos utilizados no experimento foram agrupados da seguinte maneira: (1) animais anestesiados (tratamento 1), (2) animais anestesiados e que receberam analgesia prévia (tratamento 2), (3) animais anestesiados e submetidos à orquiectomia com administração de analgésico após o processo operatório (tratamento 3) e (4) animais anestesiados e submetidos à orquiectomia com administração de analgésico antes de serem operados (tratamento 4). Os animais foram observados por cinco avaliadores em diferentes momentos: uma hora antes do procedimento cirúrgico ou anestésico (M1), quatro horas após a recuperação anestésica e antes da aplicação de analgésicos nos animais do tratamento 3 (M2), duas horas após M2 (M3) e vinte e quatro horas após a cirurgia (M4). A variável resposta (com distribuição Bernoulli) era olhar o flanco, um comportamento comum em equinos com dores abdominais. O tratamento 3 e o momento 2 foram os efeitos que apresentaram as maiores razões de chances de ocorrência da variável resposta (independente de qual metodologia estatística foi empregada na análise) quando comparados com os demais tratamentos e momentos. Ambos os modelos estatísticos ajustados aos dados (modelos 1 e 2) obtidos através das EEGs e dos MLGMs mostraram-se ser uma poderosa ferramenta para explicar a variável resposta olhar o flanco principalmente em relação a seleção das covariáveis...
Generalized linear mixed models and generalized estimating equations for binary data applied in veterinary anestehesiology
Keywords: Anestesia veterinaria; Anestesiologia; Equino - Doenças - Tratamento; Analgesicos; Modelos lineares (Estatistica); Distribuição binomial